PENGUATAN KOHESI SOSIAL MASYARAKAT ANGKOLA MELALUI PENDEKATAN AGAMA DAN BUDAYA DALAM MENINGKATKAN DAYA SAING UMKM - Suheri Harahap; Haposan Hutahaean (Studia Sosia Religia, 2026)
This article aims to identify and analyze the strengthening of social cohesion within the Angkola community through religious and cultural approaches in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs). This study employs a library research method using a qualitative and descriptive approach. The data utilized are secondary sources, including official documents, reports, scientific articles, and statistical data obtained from various government agencies and relevant institutions. Data were collected through an extensive review of literature and publications related to the role of micro-enterprises in the economic and social development of the Angkola community. The data were analyzed qualitatively by identifying, classifying, and interpreting information from multiple sources to gain a comprehensive understanding of social cohesion and the competitiveness of micro-enterprises within the Angkola society.The findings reveal that the roles of culture and religion in strengthening social cohesion among the Angkola community are reflected in various traditions and cultural practices that have been preserved across generations. Angkola local culture plays a crucial role in fostering social unity. One of the most significant traditions is Dalihan Na Tolu, which emphasizes kinship values, mutual respect, and harmonious social relationships. This cultural philosophy serves as the foundation for building fair social interactions and provides a peaceful mechanism for resolving conflicts, thereby maintaining social cohesion. Another important cultural and religious practice is the tradition of Mangitak. Initially, Mangitak referred to a traditional dish prepared exclusively for customary ceremonies due to its sacred significance for the community and the Batak kings. The preparation of Mangitak in the past involved the practice of Surat Tumbaga Hori an unwritten customary agreement known as Parpokatan or Martahi, meaning deliberation or collective discussion to prevent misunderstandings and ensure consensus among community members. Therefore, strengthening social cohesion through cultural and religious values contributes significantly to enhancing the competitiveness of MSMEs, as small enterprises function not only as economic institutions but also as instruments for community empowerment and the reinforcement of social relationships among members of society.